2010
DOI: 10.1007/s11269-010-9590-3
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of a Unique Pair of Nash Model Parameters: An Optimization Approach

Abstract: Water resources planning and management requires hydrologic models to estimate runoff from a catchment. For catchments with limited data, the choice of model and identification of its parameters is very important for development of a direct runoff hydrograph. A method is presented to determine a unique pair of hydrologic parameters of the Nash Model, number of linear cascade (n) and storage coefficient (k), using optimization based on Downhill Simplex technique. In this study physical parameters of the catchme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 51 publications
(11 citation statements)
references
References 12 publications
(11 reference statements)
0
11
0
Order By: Relevance
“…Direct impacts have been realized by means of the hydrologic cycle, which is driven primarily by climate. This has caused climatic extremes, such as floods (Ahmad and Simonovic, 2006;Ahmad et al, 2009;Ahmad et al, 2010a) and droughts (Puri et al, 2011;Stephen et al, 2010), which result in damages greater than any other form of natural disaster (Wilhite, 1997). In light of these concerns, skilful streamflow forecasts are required for the long-term planning, development, and management of water resources.…”
Section: Introductionmentioning
confidence: 99%
“…Direct impacts have been realized by means of the hydrologic cycle, which is driven primarily by climate. This has caused climatic extremes, such as floods (Ahmad and Simonovic, 2006;Ahmad et al, 2009;Ahmad et al, 2010a) and droughts (Puri et al, 2011;Stephen et al, 2010), which result in damages greater than any other form of natural disaster (Wilhite, 1997). In light of these concerns, skilful streamflow forecasts are required for the long-term planning, development, and management of water resources.…”
Section: Introductionmentioning
confidence: 99%
“…Solution to such a problem requires evaluation of the intensity of floods for various rainfall events. The rainfall-runoff process is very complicated and the problem of finding the flood magnitudes becomes more challenging when the data is limited or scantily available (Ahmad et al 2010;Bekele and Knapp 2010;Bahremand and De Smedt 2010;Ahmad 2009;Bahremand and De Smedt 2008). It requires a hydrologic model which may provide the flood magnitudes using limited parameters and data.…”
mentioning
confidence: 99%
“…Due to the above-mentioned facts, the use of geomorphology GIS, remote sensing GIUH for rainfall-runoff models for poorly gauged basins has attracted the attention of many researchers and presently a lot of work is being published in this regard (Ahmad et al 2010;Dave et al 2010;Coskun et al 2010;Cao et al 2010;Ahmad 2009;Rai et al 2009;Nguyen 2008;Sarangi et al 2007). Bhaskar et al (1997) showed that temporal distribution of rainfall excess has no marked effect on GIUH simulation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Limited availability of hydrologic data is a major hurdle for implementation of detailed hydrologic models. In cases where available data is limited, simple hydrologic models consisting of a minimum number (one or two) of model parameters are more desirable [8]. A simple conceptual model like the Muskingum model is very effective in the estimation of the hydrograph of the rise and fall of a river at any given point on the river during the course of a flood event.…”
Section: Linear Muskingum Modelmentioning
confidence: 99%